Helicobacter pylori infection and iron deficiency in patients with coronary artery disease - Fallah, S; Ahmadi, R; Moradi, N; Fadaei, R; Sezavar, S H; Seifi, M (Cellular and Molecular Biology, 2016)
The aim of this study was to investigate whether impact of the seropositivity to Helicobacter pylori (H pylori) infection on ferritin and iron levels is an independent risk factor for atherosclerosis in patients with cardiovascular disease. The anti H pylori IgG, IgA levels, serum ferritin and iron concentration of 86 patients with cardiovascular disease and 64 participants free of cardiovascular disease as control subjects were determined by ELISA assay. The results of present study showed that seropositivity to H pylori IgG and IgA levels of coronary artery disease (CAD) patients was higher than controls and CAD patients with negative anti H pylori IgG and IgA significantly. A significant negative correlation was found between seropositivity to H pylori IgG and IgA, ferritin and iron levels of CAD patients with seronegativity and seronegativity to H pylori IgG and IgA in comparison with controls. The achieved results from present study suggest that the involvement of H pylori infection in atherosclerosis process is based on the chronic inflammation which might facilitate the CAD-related pathologies. Moreover, impact of the presence of H pylori infection on reduction of the ferritin and iron levels of CAD patients as a risk factor independent of other classic factors including lipid profiles and inflammatory factors was remarkable.